The study on the impact of team learning on project performance in a shared leadership environment - xie, yuqi; Xu Ren (Journal of Modern Learning Development, 2023)
Shared leadership is an emerging and effective team leadership style. When the engineering project manager adopts the shared leadership style, the team learning of the engineering project management team is strengthened. Based on the shared leadership theory, this paper explores the impact mechanism of team learning on project performance. According to the team performance IPO theory, the relationship model between team learning, team identification and project performance is constructed. Through a questionnaire survey of 311 leaders and members of the project management team, the model was tested by using the hierarchical regression analysis method. The empirical results show that when engineering project managers adopt shared leadership, team learning and project performance are significantly positively correlated; team identity plays a partial mediating role between team learning and project performance.